Small precipitation events enhance the Eurasian grassland carbon sink. (November 2021) - Gemechu Legesse, Tsegaye; Dong, Gang; Jiang, Shicheng; Chen, Jingyan; Dong, Xiaobing; Alemu Daba, Nano; Muluneh Sorecha, Eba; Qu, Luping; Tian, Li; Shao, Changliang
Highlights: Most of the precipitation distributions were dominated by small size events. SWC has positive strong association with large size precipitation events. Small size precipitation events enhanced carbon sequestration in Mongolian grassland. The daily GPP in meadow steppe increased with increasing precipitation sizes. Abstract: Different sizes of precipitation are specifically essential in controlling plant physiological processes in ecosystems and extremely important for predicting the effects of precipitation on arid and semiarid region carbon cycle. However, the sizes of precipitation events and their role in carbon flux processes remain unclear. A consecutive three years (2014–2016) eddy covariance flux measurements were conducted to investigate the changes in carbon fluxes under different sizes of precipitation in Mongolia – typical steppe (TPL), meadow steppe (MDW) and shrubland (SHB). Most of the precipitation distributions were dominated by small size events over all sites of the study area. Gross primary productivity reached highest on days with 2 mm d −1 and 5 mm d −1 of precipitation in 2015 and 2014, respectively in TPL, whereas the highest gross primary productivity observed at 10–25 mm d −1 precipitation size in both MDW and SHB. The ecosystem respiration changed positively with different sizes of precipitation events, except for the 5 mm d −1 and 10 mm d −1 precipitation size in the study sites. There existed positive relationship between net ecosystem CO2 exchange (NEE) and small size precipitation event in both TPL and MDW. The slight association was detected between NEE and small size precipitation (<2 mm) events in SHB during the study years. By contrast, the strong relationship was observed between large precipitation sizes and NEE ( p < 0.01) in SHB. Overall, this study highlights the different responses of carbon flux to changes in the event size distribution of precipitation in grassland ecosystems which may help to predict how grassland structure and characteristic will respond to climatic change.